Language Variations Used in Stand Up Comedy Indonesia - Wawan Novianto; Siti Rofi'ah (Journal of Development Research, 2022)
Society and language are two aspects that have a very close relationship. The heterogeneous and growing nature of society gives rise to the emergence of new language variations. Register is a variation of language that appears related to the profession. There has been a lot of research on registers. But new registers are constantly emerging as new areas of life emerge. This study examines the forms of registers used by the Indonesian Stand Up Comedy community and their objectives with qualitative research methods. A total of 20 videos were carefully observed to get accurate data. The findings say the register form exists in a hierarchy of words, phrases, and shortenings. There are three types of registers, namely: technical registers, appraisal registers, and naming registers. These registers are used because they represent the context and situation in society, said Stand Up Comedy Indonesia.